Sistem Informasi Klinik GKI Raya Hankam Berbasis Desktop - Dimas Pratomo, Albertus; Sefina Samosir, Ridha; Syah Rani, Erwin (Institut Teknologi dan Bisnis Kalbis, 2019)
GKI Raya Hankam Clinic is a health service facility owned by Indonesian Christian Church. GKI Raya Hankam Clinic aims to serve health for the general public who have health problems. The purpose of this research is to build and implement a clinical information system GKI Raya Hankam based on desktop. Researcher used prototyping methods to develop systems. In research generated by information system clinic of GKI Raya Hankam based on desktop can help patient data storage, drug data, record transactions and print receipt or payment transactions. This system can also help search patient data and drugs if the user wants to find the required data. The existence of this clinical information system, clinic of GKI Raya Hankam can easily meet the needs and manage patient data, medicine and payment.